Penelitian Ekonomi Teknik dalam IHS Konstruksi Beton Mutu Tinggi (Universitas Esa Unggul, 2006)
AbstractThis research is connected with index unit price which is used in the process of design and construction of setting up high quality concrete building in accordance with Law No. 28/2002. Method of research used is by utilizing nomenklatur of building accompanied with identification of primary elements, encompassing remuniration, dominant material and method of accomplishment. Then, conduct identification for verification along with the result of field survey which is further continued with analysis of index unit price. The result of engineering economy research denotes that from 3 types of researched buildings acquires rate of percentage toward AHS: remuniration = 21,5 %, material = 75,9% and method of accomplishment = 2,6%. The result of this research also reveals 4 types of materials which determines cost of material, that is: concrete, steel, bricks, and wood. This research concludes that cost of material still dominates cost of construction. In other word, understanding sensitivity of cost for material will influence cost of construction. Kata Kunci: Ekonomi Teknik, Indeks Harga Satuan, Konstruksi Bangunan, Beton Mutu TInggi.